The 3 tenors in concert, 1994 [videorecording (DVD)] - Rudas, Tibor; Carreras, José; Domingo, Plácido, 1941-; Pavarotti, Luciano; Mehta, Zubin (Kultur, 2010)
"Recorded live on stage on the eve of one of the world's greatest sporting events, The 3 tenors in concert, 1994 re-unites four of classical music's premier and most popular talents."--Container.